How we do it : the evolution and future of human reproduction - Martin, R. D. (Robert D.), 1942- (Basic Books, 2013)
"Despite our seemingly endless fascination with sex and parenting, the origins of our reproductive lives remain a mystery. Why are a quarter of a billion sperm cells needed to fertilize one egg? Are women really fertile for only a few days each month? How long should women breast-feed? In [this book], primatologist Robert Martin draws on forty years of research to locate the origins of everything from sex cells to baby care, and to reveal what's really natural when it comes to making and raising babies. He acknowledges that although it's not realistic to reproduce like our ancestors did, there are surprising consequences to behavior we take for granted, such as bottle feeding, cesarean sections, and in vitro fertilization"--Amazon.com.